2011
DOI: 10.3233/jad-2010-101593
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Apigenin Protects Brain Neurovascular Coupling against Amyloid-β25-35-Induced Toxicity in Mice

Abstract: Apigenin, one of the most common flavonoids, has demonstrated anti-inflammatory, anticarcinogenic, and free radical-scavenging activities. Recent studies revealed its protective effects against amyloid-β (Aβ)-induced neurotoxicity, but the mechanism was unclear. In the present study, we aimed to explore the anti-amnesic and protective effects of apigenin against Aβ₂₅₋₃₅-induced toxicity and the underlying mechanisms in the cerebral cortex in mice. The learning and memory impairments, changes in morphology of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 0 publications
1
48
1
Order By: Relevance
“…Rice-Evans et al6 reported that upon measuring an alternate antioxidant activity marker such as Trolox-equivalent antioxidant activity (TEAC) in various flavonoid compounds, apigenin had greater antioxidant activity than kaempferol, and all other flavonoid compounds still had higher antioxidant activity than Trolox. The present study found that apigenin had negligible free radical DPPH scavenging activity as well as no influence on Aβ-induced neuronal death, which is not compatible with the findings of previous studies 6,35. This result may be due to the use of free radical DPPH scavenging activity, which better reflects antioxidant activity on Aβ compared with TEAC.…”
Section: Discussioncontrasting
confidence: 99%
“…Rice-Evans et al6 reported that upon measuring an alternate antioxidant activity marker such as Trolox-equivalent antioxidant activity (TEAC) in various flavonoid compounds, apigenin had greater antioxidant activity than kaempferol, and all other flavonoid compounds still had higher antioxidant activity than Trolox. The present study found that apigenin had negligible free radical DPPH scavenging activity as well as no influence on Aβ-induced neuronal death, which is not compatible with the findings of previous studies 6,35. This result may be due to the use of free radical DPPH scavenging activity, which better reflects antioxidant activity on Aβ compared with TEAC.…”
Section: Discussioncontrasting
confidence: 99%
“…In the past few years, this compound has aroused huge interest as a potential chemotherapeutic agent owing to its low intrinsic toxicity and notable results on normal versus cancerous cells, compared with other structurally similar flavonoids (Madunić et al, 2018). Regarding its antioxidant effects, it was verified that apigenin down regulates adhesion molecules (Liu et al, 2011), while suppressing oxidative stress through its direct free radical scavenging action and upregulating intracellular antioxidant defences. Although displaying high antioxidant activity in vitro, assessed via different methods, the low intestinal absorption of apigenin verified in a Caco-2 cell monolayers model, indicates that encapsulation may be mandatory to enhance its bioavailability for applications as oral antioxidant drug/supplement (Pérez-Sánchez et al, 2017).…”
Section: Evaluation Of Bioactive Propertiesmentioning
confidence: 99%
“…In vivo treatment with luteolin protected mice brain from traumatic brain injury by inhibiting inflammatory response and inducing autophagy [30]. Apigenin also protected rat and mice neurons against Aβ-induced neurotoxicity [31,32]. Although the biological functions of luteolin and apigenin are well-known, few studies have investigated their effects to protect neuronal-like catecholaminergic PC12 cells from 4-HNE-mediated cytotoxicty with a special focus on UPR and hormetic cellular stress-response pathways involved.…”
Section: Introductionmentioning
confidence: 99%